The Impact of Gymnastics on Children's Physical Self-Concept and Movement Skill Development in Primary Schools. Issue 2 (3rd April 2017) - Rudd, J. R.; Barnett, L. M.; Farrow, D.; Berry, J.; Borkoles, E.; Polman, Remco
ABSTRACT: This study evaluated the effectiveness of an 8-week gymnastics curriculum on children's movement competence and their physical self-concept. There were 113 children (46% girls, 49% intervention) with a mean age of 9.4 years ( SD = 1.8) that participated. Intervention children underwent 8 weeks of gymnastics and the comparison group continued with their standard curriculum. Age was a significant co-variate, a separate analysis was conducted on the lower (grades 2 and 4) and upper (grade 6) groups. The lower age group showed significant improvement in favor of the gymnastic group in fundamental movement skills. The upper age group showed a significant improvement for the control group in general body coordination and fundamental movement skills. For all grades, the physical self-concept showed a significant main effect in favor of the gymnastics group. The gymnastics intervention was found to be of particular benefit for developing children's movement competence and physical self-concept in younger children.